Today's Apartment Architecure - Broto, Carles (Singapore: Page One, 2006)
The projects in this volume illustrate the latest tendencies in collective housing. Conventional vertical dwellings, buildings for specific groups and residential complexes share a common spirit: rigour, imagination and respect for both the persons who will occupy them and the enviroment in which they will be located. The works of Frank O. Gehry, Claus en Kaan Architecten, Herzog & de Meuron, Alvaro Siza, Mecano, to name just a few of the architects included in this book, provide stimulating answers, ingenious solutions, unexpected points of view and proposals that will without doubt influence the conception of residential architecture in the century to come.
Include bibliogrpical references
Keywords: Apartment Houses